Sponsored links: Algebra eBooks
 

Related

ssubst-string

S_Einheit: km/h;

S_Formel: s/t;

sechs_S: ssubst("h","...

Calculate

ssubst-string

f:3;

d:string(a+b/c);

e:ssubst("f","a",d);

Calculate

ssubst-subst

ssubst(".",",","x/10+...

Calculate

ssubst

eq1: H_1= -w^2*M_c+K_...

eq2: H_2= -w^2*M_s+K_...

eq3: H_12= K_s-%i*w*C_s;

Calculate

ssubst-subst

ssubst(".",",","x/10+...

Calculate

ssubst

eq1: H_1= -w^2*M_c+K_...

eq2: H_2= -w^2*M_s+K_...

eq3: H_12= K_s-%i*w*C_s;

Calculate

ssubst

eq1: H_1= -w^2*M_c+K_...

eq2: H_2= -w^2*M_s+K_...

eq3: H_12= K_s-%i*w*C_s;

Calculate

ssubst-string

S_Einheit: t/s;

S_Formel: h/km;

testvalue: 0;

Calculate

ssubst

Run Example
(%i1)is(equal((ssubst(".",",","x/10+1,9/x^9")),ev(x/10+1.9/x^9)));
(%o1)                                false
(%i2) 
Run Example
if is(abs(eval_string(ssubst(".",",","183,5113"))-183.5113948044)<
=0.0005) then 1 elseif is(abs(183,5113-integrate(integrate(integrate(2,x,0,null),y,0,null),z,0,null))<
=0.0005) then 0.5*1 else 0.0;
(%o1)                                  1
(%i2) 
Run Example
eq1: H_1= -w^2*M_c+K_c+K_s+%i*w*(C_c+C_s);
                              2
(%o1)            H_1 = - M_c w  + %i (C_s + C_c) w + K_s + K_c
(%i2) eq2: H_2= -w^2*M_s+K_s+%i*w*C_s;
                                     2
(%o2)                   H_2 = - M_s w  + %i C_s w + K_s
(%i3) eq3: H_12= K_s-%i*w*C_s;
(%o3)                        H_12 = K_s - %i C_s w
(%i4) eq4: S= S_o/w^2*(H_12-H2)*(K_c+%i*w*C_c)/(H_1*H_2-H_12^2);
                         S_o (%i C_c w + K_c) (H_12 - H2)
(%o4)                S = --------------------------------
                                2                2
                               w  (H_1 H_2 - H_12 )
(%i5) eq5: K_c = w_c^2*M_c;
                                             2
(%o5)                           K_c = M_c w_c
(%i6) eq6: K_s = w_s^2*M_s;
                                             2
(%o6)                           K_s = M_s w_s
(%i7) eq7: C_s=d_s*M_s;
(%o7)                            C_s = d_s M_s
(%i8) eq8: C_c=d_c*M_c;
(%o8)                            C_c = d_c M_c
(%i9) eq9: M_c=n*M_ssubst([eq1,eq2,eq3],eq4);
                                     2
(%o9) M_c = n M_ssubst([H_1 = - M_c w  + %i (C_s + C_c) w + K_s + K_c, 
             2
H_2 = - M_s w  + %i C_s w + K_s, H_12 = K_s - %i C_s w], 
    S_o (%i C_c w + K_c) (H_12 - H2)
S = --------------------------------)
           2                2
          w  (H_1 H_2 - H_12 )
(%i10) subst ([eq5,eq6,eq7,eq8,eq9], subst([eq1,eq2,eq3],eq4));
                               2
(%o10) S = (S_o (- H2 + M_s w_s  - %i d_s M_s w)
       2                        2
 (n w_c  M_ssubst([H_1 = - M_c w  + %i (C_s + C_c) w + K_s + K_c, 
             2
H_2 = - M_s w  + %i C_s w + K_s, H_12 = K_s - %i C_s w], 
    S_o (%i C_c w + K_c) (H_12 - H2)
S = --------------------------------) + %i d_c n w
           2                2
          w  (H_1 H_2 - H_12 )
                        2
 M_ssubst([H_1 = - M_c w  + %i (C_s + C_c) w + K_s + K_c, 
             2
H_2 = - M_s w  + %i C_s w + K_s, H_12 = K_s - %i C_s w], 
    S_o (%i C_c w + K_c) (H_12 - H2)
S = --------------------------------)))
           2                2
          w  (H_1 H_2 - H_12 )
   2          2        2                                                     2                                              2                                               S_o (%i C_c w + K_c) (H_12 - H2)                    2                        2                                              2                                               S_o (%i C_c w + K_c) (H_12 - H2)       2                        2
/(w  ((M_s w_s  - M_s w  + %i d_s M_s w) (%i w (d_c n M_ssubst([H_1 = - M_c w  + %i (C_s + C_c) w + K_s + K_c, H_2 = - M_s w  + %i C_s w + K_s, H_12 = K_s - %i C_s w], S = --------------------------------) + d_s M_s) + n w_c  M_ssubst([H_1 = - M_c w  + %i (C_s + C_c) w + K_s + K_c, H_2 = - M_s w  + %i C_s w + K_s, H_12 = K_s - %i C_s w], S = --------------------------------) - n w  M_ssubst([H_1 = - M_c w  + %i (C_s + C_c) w + K_s + K_c, 
                                                                                                                                                                                   2                2                                                                                                                                                          2                2
                                                                                                                                                                                  w  (H_1 H_2 - H_12 )                                                                                                                                                        w  (H_1 H_2 - H_12 )
             2
H_2 = - M_s w  + %i C_s w + K_s, H_12 = K_s - %i C_s w], 
    S_o (%i C_c w + K_c) (H_12 - H2)           2
S = --------------------------------) + M_s w_s )
           2                2
          w  (H_1 H_2 - H_12 )
           2                2
 - (M_s w_s  - %i d_s M_s w) ))
(%i11) 

Related Help

Help for Ssubst